The role of PANDER and its interplay with IL-6 in the regulation of GLP-1 secretion - Li, Zeting; Pei, Ling; Xiao, Huangmeng; Chen, Nan; Lai, Fenghua; Yue, Shufang; Xu, Changliu; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (Endocrine Connections, 2024)
Glucose-like peptide-1 (GLP-1) is a vital hormone in the intestines that regulates glucose metabolism. Although pancreatic-derived factor (PANDER) overexpression is known to suppress GLP-1, the underlying mechanisms are unclear. Our study aims to uncover how PANDER influences GLP-1 synthesis and secretion. We established a PANDER overexpression model in STC-1 intestinal cells, confirming its inhibitory effect on GLP-1 secretion. This effect was reversed in PANDER-knockout cells. Additionally, a negative correlation between PANDER and GLP-1 was observed in patients with a history of gestational diabetes. Subsequently, through whole transcriptome gene sequencing in PANDER-overexpressed STC-1 cells, we discovered that the activation of IL-6 and its related STAT3 signaling pathway was significantly inhibited, and this finding was validated by Western blotting and quantitative reverse transcription PCR. Finally, rescue experiments confirmed that the IL-6-related STAT3/Akt/GSK3β/β-catenin signaling pathway mediates the negative regulatory effect of PANDER on GLP-1. Taken together, our data identify IL-6 as a bridge connecting PANDER and GLP-1 in the STC-1 cells, demonstrating potential therapeutic targets for diabetes treatment by targeting the PANDER–IL-6–GLP-1 axis.